Relationship among cost of financial intermediation, risk, and efficiency: Empirical evidence from Bangladeshi commercial banks - Anupam Das Gupta; Niluthpaul Sarker; Mohammad Rifat Rahman (Cogent Economics & Finance, 2021)
The global financial crisis and stiff market competition enhance risk exposures that raise debate on the cost of financial intermediation and the supremacy of banks' efficiency. This study examines the concurrent effects of bank risk, efficiency and cost of financial intermediation of Bangladeshi commercial banks. The Two-Step System GMM (2GMM) estimators of unbalanced dynamic panel data of 32 commercial banks from 2000 to 2016 addresses key factors rigorously in the light of bank-level, industry-level, and macroeconomic-level phenomenon. Efficiency gains cost the spread of banks' financial intermediation, and risk-taking negatively affects the return. Cost-efficient banks are taking more credit risk; however, more efficiency gains reduce banks' risk substantially. Size (cost of intermediation) of banks positively (inversely) affect the risk-taking (efficiency) behaviour of banks. Market competition enhances the risk and efficiency and reduces banks' interest spread. Finally, the Nonlinear effect of size and market competition is heterogeneous on risk, efficiency, and financial intermediation cost that follows a U-shape curve. This study explicitly addresses two issues: simultaneous effect of financial intermediation, bank risk, and efficiency and validated the nonlinear relationship considering size and market competition effect.
Keywords: C2; D61; G17; G21; 330; Cost of financial intermediation; efficiency; GMM estimators; market competition; risk